Efectos en el rendimiento físico a corto plazo de dos programas de entrenamiento neuromuscular con diferente orientación aplicados en jugadores de fútbol de élite U-17 - Raya-Gonzalez, J.; Suarez-Arrones, L.; Moreno-Puentedura, M.; Ruiz-Marquez, J.; Saez de Villarreal, E. (Revista Internacional de Ciencias del Deporte, 2017)
The aim of this research was to compare the effects of two different neuromuscular training programs (vertical vs. horizontal orientation), conducted during 6 weeks, on the physical performance of soccer players in-season. Sixteen soccer players of 16.6 ± 0.3 years were randomly assigned to two equally large experimental groups, and both supplemented the soccer training with a specific neuromuscular training program 2 days/week. Vertical group´s training (n=8, VG) was composed by half-squat using a flywheel device and vertical jump to box and horizontal group´s training (n=8, HG) consisted on linear and non-linear resisted sprints. Before and after the training period jumping ability, linear and non-linear sprint and lower-limb power were measured. Substantial improvements (likely to very likely) were found in the VG in countermovement jump (CMJ) (ES: 0.49), Abalakov test (ABK) (ES: 0.38) and Mean Propulsive Velocity (all load measured), in addition to decrease the performance in linear and non-linear sprint (COD-L). The HG improved substantially in 10m sprint (Effect size [ES]: 0.63), COD-R (ES: 0.36), COD-L (ES: 0.34) and in Mean Propulsive Velocity in 15-30-50kg. Furthermore, a possible improvement in 20 and 30m sprint was also reported in HG. Between-groups analysis showed greater substantial improvements in VG in CMJ (ES: 0.39), and in HG in 10-20-30m sprint and COD-R. The results obtained suggest that horizontal group´s training program could be more effective in order to optimize the specific physical condition of the soccer players.